Deflection bowls in flexible pavement structures - Higuera-Sandoval, Carlos Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The loads imposed by the traffic on the elastic flexible pavement structures generate the so-called deflection basins, which affect the structural and functional operation of a flexible pavement structure and, therefore, its useful life. The purpose of this work is to show the effect of the maximum load of the tractor-type truck-trailer C3S3- on the deflection of a flexible pavement structure and to model its corresponding deflection bowl in a three-dimensional system. The deflection analysis is made taking into account a flexible reference pavement structure, consisting of an asphalt tread layer, a granular base layer and a granular sub-base layer, supporting the entire structural package on the subgrade. The SHELL BISAR 3.0 program was used to model the deflection basins, which allows calculating the stresses, deformations and deflections at any point in the structure of the flexible pavement structural model. Finally, some recommendations are presented that must be taken into account in the structural and functional design of a pavement structure.This article is part of the research on the behavior of deflection based on the design parameters of a pavement structure, which the author has been advancing at the School of Transport and Roads, Faculty of Engineering of the Pedagogical and Technological University of Colombia , in the Research and Development Group on Road Infrastructure -GRINFRAVIAL-.